THE COMPARISON ANALYSIS OF PRICE TOWARDS QUALITY, HOSPITALITY, AND DESIGN BETWEEN FOUR POINTS HOTEL AND LAGOON HOTEL - Kindangen, Indah Rani Jessica; Pangemanan, Sifrid S.; Tumiwa, Johan . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Hotel Lagoon and Four Points have a place in the central shopping area and both hotels are very strategic, access to go to the mall is very easy. which makes this hotel has a difference is to parked in the lagoon hotel is very easy to find and the location of the hotel lagoon is quite far from the streets, lagoon hotel is located behind the Bahu Mall, while for Four Points own place one with Manado Town Square, for parking also had to share with Mantos and in the end it was difficult to find an empty parking lot. The location of the four points hotel is close to the streets so for access using public transport more easily. the price offered is also different. for the size of hotels such as lagoon can be categorized as luxury hotel but the price given by the hotel is cheaper than the four points hotel. while the price offered by four points higher., in terms of hospitality Hotel Lagoon has employees who cater to visitors very friendly and faster to respond than the Four Points, and seen from the design Lagoon has a spot to take pictures for the hobby by taking pictures and also distinguishes the Lagoon and Four points from its design, for the building design between the Lagoon and the more luxurious Four Points Lagoon than the Four Points. Keywords: price, hospitality, design